2003
DOI: 10.1258/096914103771773294
|View full text |Cite
|
Sign up to set email alerts
|

The burden of prevention: downstream consequences of Pap smear testing in the elderly

Abstract: Context:Although cervical cancer is an unusual cause of death among women 65 and older, most elderly women in the US report continuing to undergo periodic Pap smear screening. Objective: Conclusion:Cervical cancer screening is widespread among elderly American women, and follow-up testing is not uncommon, particularly among the ten percent of women who appear to be in a cycle of repeated testing. This substantial volume of testing occurs despite the rarity of cervical cancer deaths and unknown bene ts of scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Until recently recommendations from the US have been for women to be screened into their 80 s, and cervical screening over age 65 y is common [3],[4]. The current recommendation from both the American Congress of Obstetricians and Gynecologists and the American Cancer Society is that screening should be stopped at age 65 y for women with evidence of adequate prior negative screening and no history of cervical intraepithelial neoplasia grade 2+ [5],[6], but this recommendation was based only on expert opinion and modelling because of the lack of empirical data.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently recommendations from the US have been for women to be screened into their 80 s, and cervical screening over age 65 y is common [3],[4]. The current recommendation from both the American Congress of Obstetricians and Gynecologists and the American Cancer Society is that screening should be stopped at age 65 y for women with evidence of adequate prior negative screening and no history of cervical intraepithelial neoplasia grade 2+ [5],[6], but this recommendation was based only on expert opinion and modelling because of the lack of empirical data.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of unanimity about CC screening in the elderly reflects the uncertainty regarding the cost-effectiveness ratio of Pap cytology within the postmenopausal (PMP) population 7. The efficacy of cytological screening is known to be lower in higher age groups, when compared with women aged 30–35 years, and is only effective in 20% of women aging 50 years or older 9.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 For example, in one study, two-thirds of American adults wanted a cancer screening test even when nothing could be done about the cancer if detected. 12 Overuse of screening tests (e.g., screening when there is no evidence that the test will benefit patient outcomes) have been reported for colorectal cancer, 14 cervical cancer, 15,16 and breast cancer. 17 One large, nationally representative study of the United States reported that 45% of older adults had been overscreened for colorectal, cervical, or breast cancer.…”
mentioning
confidence: 99%